Strategic Policy for the Development of Tanjung Lesung Tourist Destination as A Special Economic Zone in Banten Province - Nugroho, Arif; Jumanah, Jumanah; Stiawati, Titi (Universitas Muhammadiyah Gorontalo, 2025)
Special Economic Zone (SEZ) Tanjung Lesung, designated under Government Regulation Number 26 of 2012, holds significant potential as a premier tourist destination in Banten Province. However, after more than five years of operation, the development of this area has not been optimal. It has yet to deliver a significant impact on the national, regional, and local economies. This study aims to identify the key tourist destination potentials within SEZ Tanjung Lesung. A qualitative approach was employed, utilizing both primary and secondary data collection methods, including field observations, documentation, interviews with relevant stakeholders, and literature review. The findings indicate that SEZ Tanjung Lesung possesses substantial potential in the tourism sector, particularly due to its attractive beach tourism, strong support from central and regional governments, and readiness of human resources. However, the main challenges faced include limited investment capital, inadequate supporting facilities and infrastructure, and difficult accessibility from urban centers. The alignment between the master plan and the existing conditions remains low, indicating discrepancies between planning and actual implementation on the ground. This study recommends improvements in the planning and policy implementation for the development of SEZ Tanjung Lesung, including enhancing infrastructure, facilitating investment, and strengthening human resource capacities to achieve sustainable development goals and positively impact the regional economy.